Legal space for syringe exchange programs in hot spots of injection drug use-related crime. Issue 1 (December 2016) - Allen, Sean; Ruiz, Monica; Jones, Jeff; Turner, Monique
Abstract Background Copious evidence indicates that syringe exchange programs (SEPs) are effective structural interventions for HIV prevention among persons who inject drugs (PWID). The efficacy of SEPs in supporting the public health needs of PWID populations is partially dependent on their accessibility and consistent utilization among injectors. Research has shown that SEP access is an important predictor of PWID retention at SEPs, yet policies exist that may limit the geographic areas where SEP operations may legally occur. Since 2000 in the District of Columbia (DC), SEP operations have been subject to the 1000 Foot Rule (§48–1121), a policy that prohibits the distribution of "any needle or syringe for the hypodermic injection of any illegal drug in any area of the District of Columbia which is within 1000 feet of a public or private elementary or secondary school (including a public charter school)." The 1000 Foot Rule may impede SEP services in areas that are in urgent need for harm reduction services, such as locations where injections are happening in "real time" or where drugs are purchased or exchanged. We examined the effects of the 1000 Foot Rule on SEP operational space in injection drug use (IDU)-related crime (i.e., heroin possession or distribution) hot spots from 2000 to 2010. Methods Data from the DC Metropolitan Police Department were used to identify IDU-related crime hot spots. School operation data were matched to a dataset that described the approximate physical property boundaries of land parcels. A 1000-ft buffer was applied to all school property boundaries. The overlap between the IDU-related crime hot spots and the school buffer zones was calculated by academic year. Results When overlaying the land space associated with IDU-related crime hot spots on the maps of school boundaries per the 1000-ft buffer zone stipulation, we found that the majority of land space in these locations was ineligible for legal SEP operations. More specifically, the ineligible space in the identified hot spots in each academic year ranged from 51.93 to 88.29 % of the total hot spot area. Conclusions The removal of the 1000 Foot Rule could significantly improve the public health of PWID via increased access to harm reduction services. Buffer zone policies that restrict SEP operational space negatively affect the provision of harm reduction services to PWID.